Critical appraisal of clinical practice guidelines for treating pancreatic cancer based on the global disease burden. Issue 1 (February 2015) - Li, Cui Cui; Wang, Ying Qiang; Li, You Ping; Li, Xiang Lian
Abstract: Objectives: To evaluate the quality of pancreatic cancer guidelines with evidence‐based methods based on the global burden of disease and to explore its status, distribution, characteristics of theme, and the difference of recommended therapies among various qualities of guidelines, so as to provide a reference for clinical decision. Methods: The PubMed, The Cochrane Library (Issue 11, 2013), Chinese Biomedical Database, China National Knowledge Infrastructure, and VIP databases, as well as the website of National Guidelines Clearinghouse, Guidelines International Network, and National Institute for Clinical Excellence were systematically reviewed through November 2013 for pancreatic cancer guidelines. The Appraisal of Guidelines for Research and Evaluation (AGREE II) were applied to assess the methodological quality of the guidelines. Results: A total of 14 relevant guidelines (including 5 evidence‐based ones) were identified, involving four continents (Asia, Europe, North America, and Oceania), seven counties, and four international organizations. There were only two domains, namely 'scope and purpose' and 'clarity of presentations', getting high average scores (more than 60%) among all 14 guidelines. The mean AGREE domain score in guidelines varies among different areas, and the quality of 5 evidence‐based guidelines was superior to that established by consensus. According to AGREE II, 11 guidelines were weakly recommended, while 3 were not recommended due to poor methodological quality. Their subjects of 14 guidelines covered six treatment categories, including chemotherapy, surgery, radiotherapy, support therapy, radiotherapy, and interventional therapy. Conclusion: The overall methodological quality of pancreatic cancer guidelines is suboptimal among different countries or regions. The qualities of evidence‐based guidelines are significantly superior to consensus. The chemotherapy, surgery, radiotherapy, and support therapy were the predominant choices by guidelines.